Flexible self-supporting positive plate as well as preparation method and application thereof

Flexible self-supporting positive electrode sheets were prepared through electrospinning technology, and the structural stability was enhanced by vanadium nitride-vana oxide composite, which solved the problem of structural collapse in vanadium pentoxide zinc ion capacitors, and achieved high cycling stability and high capacity electrode materials.

CN120565302APending Publication Date: 2025-08-29展长振
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510634675.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

When vanadium pentoxide is the electrode material for zinc ion capacitors, the large hydration radius of zinc ions leads to weakening of the van der Waals force between layers, resulting in collapse of the electrode material structure, which in turn reduces the capacity of the capacitor, deteriorates the cycle stability, and has a low cycle retention rate.

Method used

The flexible self-supporting positive electrode sheet was prepared by electrospinning technology. By dissolving PAN and vanadium pentoxide in DMF, post-electrospinning heat treatment and inert atmosphere heating, the vanadium nitride-vacaner oxide composite was formed, the structural stability of the electrode material was enhanced, and the porous nanofiber structure was formed by doping carbon fiber matrix and nitrogen elements, shortening the ion and electron transport paths, and improving the electrochemical performance of the electrode material.

Benefits of technology

The cyclic stability of the electrode material is significantly improved, the structure is prevented from collapse, the cyclic performance of the electrode is improved, the capacity retention rate reaches more than 97%, and the electrochemical performance of the electrode material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005406337460000071
    Figure BDA0005406337460000071
  • Figure BDA0005406337460000081
    Figure BDA0005406337460000081
Patent Text Reader

Abstract

The invention discloses a preparation method of a flexible self-supporting positive plate, which comprises the following steps: dissolving PAN (Polyacrylonitrile) and vanadium pentoxide in a DMF (Dimethyl Formamide) solvent to form a spinning solution, and then preparing a nanofiber spinning material through an electrostatic spinning process. And carrying out multi-stage heat treatment on the spinning material in an air atmosphere, an inert gas atmosphere and a nitrogen-containing gas atmosphere in sequence to finally prepare the flexible self-supporting positive plate. According to the method, the electrostatic spinning technology is adopted, effective compounding of the vanadium element and the carbon fiber matrix and nitrogen element doping of the carbon fiber are achieved, the prepared porous nanofiber structure can effectively shorten the transmission path of ions and electrons, the contact specific surface area of the electrode material and an electrolyte is remarkably increased, and the electrochemical performance of the electrode material is improved. Therefore, the electrochemical performance of the electrode material is greatly improved. In addition, through the synergistic effect of vanadium nitride and vanadium oxide, the structural stability of the electrode material is effectively enhanced, structural collapse in the circulation process is prevented, and the circulation stability of the electrode is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode materials, and in particular to a flexible self-supporting positive electrode sheet and a preparation method and application thereof. Background Art

[0002] Over the past few decades, electrochemical capacitors, also known as supercapacitors, have attracted widespread attention as an important electrochemical energy storage device. Electrochemical capacitors have higher power density than batteries and higher energy density than traditional dielectric capacitors, making them a bridge between batteries and traditional dielectric capacitors. Due to their cycle life of up to 100,000 times and their ability to charge and discharge rapidly in a short period of time, electrochemical capacitors are also competitive energy storage devices. Electrochemical capacitors will play an equally important role as batteries in the future energy storage field. Potential applications of electrochemical capacitors include electric vehicles, hybrid electric vehicles, portable electronic devices, and smart grids as the main and auxiliary energy sources for electrochemical energy storage.

[0003] Currently, the electrode materials for aqueous zinc-ion capacitors primarily include manganese oxides, Prussian blue, quinone analogs, and vanadium oxides. The multivalent nature of vanadium in vanadium pentoxide and its layered oxide structure facilitate the efficient insertion and extraction of zinc ions. However, when used as an electrode material for zinc-ion capacitors, the large hydration radius of zinc ions weakens the interlayer van der Waals forces during the insertion and extraction process, leading to structural collapse of the electrode material. This in turn reduces the capacitor's capacity, deteriorates cycling stability, and reduces cycle retention. Therefore, a new solution is necessary to address these issues. Summary of the Invention

[0004] In view of this, the present invention addresses the deficiencies in the prior art and its main purpose is to provide a flexible, self-supporting positive electrode sheet and its preparation method and application, which can effectively solve the problem that the electrode material of the existing zinc ion capacitor is weakened by the interlayer van der Waals force of vanadium pentoxide, resulting in structural collapse of the electrode material, and thus reducing the capacitor capacity, poor cycle stability, and low cycle retention rate.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a flexible self-supporting positive electrode sheet comprises the following steps:

[0007] (1) dissolving PAN and vanadium pentoxide in DMF, wherein the mass ratio of PAN, vanadium pentoxide, and DMF is 1: (0.2-0.6): 9, to obtain a spinning solution;

[0008] (2) electrospinning the spinning solution obtained in step (1) to obtain a spun material;

[0009] (3) placing the spun fabric obtained in step (2) in an air atmosphere for heat treatment and pre-oxidation, the heat treatment temperature is 200° C., and the heat treatment time is 1-3 hours to obtain a pre-oxidized spun fabric;

[0010] (4) The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 800-1000°C in an inert gas atmosphere, and then kept warm for 1-2 hours. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 1-50 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet.

[0011] As a preferred embodiment, in step (4), the inert gas is argon.

[0012] As a preferred embodiment, in step (4), the nitrogen-containing gas is ammonia.

[0013] A flexible zinc ion capacitor, wherein the positive electrode sheet is a positive electrode sheet prepared by the above-mentioned method for preparing a flexible self-supporting positive electrode sheet; and the solid electrolyte is a PVA gel with zinc salt as a solute.

[0014] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0015] The use of electrospinning technology not only achieves the effective compounding of vanadium with the carbon fiber matrix and the nitrogen doping of the carbon fibers, but also the resulting porous nanofiber structure effectively shortens the transmission path of ions and electrons, significantly increasing the contact surface area between the electrode material and the electrolyte, thereby significantly improving the electrochemical performance of the electrode material. Furthermore, the synergistic effect of vanadium nitride and vanadium oxide effectively enhances the structural stability of the electrode material, preventing structural collapse during cycling and significantly improving the cycling stability of the electrode.

[0016] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below with reference to specific embodiments: DETAILED DESCRIPTION

[0017] The present invention discloses a method for preparing a flexible self-supporting positive electrode sheet, which comprises the following steps:

[0018] (1) dissolving PAN and vanadium pentoxide in DMF, wherein the mass ratio of PAN, vanadium pentoxide, and DMF is 1: (0.2-0.6): 9, to obtain a spinning solution;

[0019] (2) electrospinning the spinning solution obtained in step (1) to obtain a spun material;

[0020] (3) placing the spun fabric obtained in step (2) in an air atmosphere for heat treatment and pre-oxidation, the heat treatment temperature is 200° C., and the heat treatment time is 1-3 hours to obtain a pre-oxidized spun fabric;

[0021] (4) transferring the pre-oxidized spinning product obtained in step (3) to a tubular furnace, introducing an inert gas, heating to 800-1000° C. in an inert gas atmosphere, and then keeping the temperature for 1-2 hours. Then, introducing a nitrogen-containing gas, exhausting the inert gas, and keeping the temperature for 1-50 minutes in an atmosphere of nitrogen-containing gas to obtain a positive electrode sheet; the positive electrode sheet is loaded with vanadium nitride-vanadium oxide. The compounding of vanadium nitride and vanadium oxide not only enables the obtained carbon fiber non-woven fabric to have the performance improvement brought by the compounding of the two compounds, but also forms a synergistic effect. Through the heterojunction structure between vanadium oxide and vanadium nitride, the structural stability of the electrode material is effectively enhanced, the structural collapse during the cycle is prevented, and the cycle stability of the electrode is significantly improved. The inert gas is argon, and the nitrogen-containing gas is ammonia. The vanadium-oxygen-nitrogen ratio in the flexible self-supporting positive electrode sheet of the final product can be controlled by controlling the holding time in the nitrogen-containing gas atmosphere.

[0022] In addition, the present invention also discloses a flexible zinc ion capacitor, wherein the positive electrode sheet is a positive electrode sheet prepared by the aforementioned method for preparing a flexible self-supporting positive electrode sheet; and the solid electrolyte is a PVA gel with a zinc salt as a solute.

[0023] The following describes the details in conjunction with multiple embodiments.

[0024] Example 1

[0025] (1) PAN and vanadium pentoxide are dissolved in DMF, with the mass ratio of PAN, vanadium pentoxide and DMF being 1:0.4:9, to obtain a spinning solution.

[0026] (2) The spinning solution obtained in step (1) is subjected to electrostatic spinning to obtain a spun product.

[0027] (3) The spun fabric obtained in step (2) is placed in an air atmosphere for heat treatment and pre-oxidation at a temperature of 200° C. for 1 h to obtain a pre-oxidized spun fabric.

[0028] (4) The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 900°C in an inert gas atmosphere, and then kept warm for 1 hour. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 40 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet; the inert gas is argon, and the nitrogen-containing gas is ammonia.

[0029] Example 2

[0030] (1) PAN and vanadium pentoxide are dissolved in DMF, with the mass ratio of PAN, vanadium pentoxide and DMF being 1:0.4:9, to obtain a spinning solution.

[0031] (2) The spinning solution obtained in step (1) is subjected to electrostatic spinning to obtain a spun product.

[0032] (3) The spun fabric obtained in step (2) is placed in an air atmosphere for heat treatment and pre-oxidation at a temperature of 200° C. for 2 h to obtain a pre-oxidized spun fabric.

[0033] (4) The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 800°C in an inert gas atmosphere, and then kept warm for 2 hours. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 20 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet; the inert gas is argon, and the nitrogen-containing gas is ammonia.

[0034] Example 3

[0035] (1) Dissolve PAN and vanadium pentoxide in DMF, with the mass ratio of PAN, vanadium pentoxide and DMF being 1:0.2:9, to obtain a spinning solution.

[0036] (2) The spinning solution obtained in step (1) is subjected to electrostatic spinning to obtain a spun product.

[0037] (3) The spun fabric obtained in step (2) is placed in an air atmosphere for heat treatment and pre-oxidation at a temperature of 200° C. for 2.5 h to obtain a pre-oxidized spun fabric.

[0038] (4) The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 1000°C in an inert gas atmosphere, and then kept warm for 2 hours. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 20 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet; the inert gas is argon, and the nitrogen-containing gas is ammonia.

[0039] Example 4

[0040] (1) PAN and vanadium pentoxide are dissolved in DMF, with the mass ratio of PAN, vanadium pentoxide and DMF being 1:0.3:9, to obtain a spinning solution.

[0041] (2) The spinning solution obtained in step (1) is subjected to electrostatic spinning to obtain a spun product.

[0042] (3) The spun fabric obtained in step (2) is placed in an air atmosphere for heat treatment and pre-oxidation at a temperature of 200° C. for 1.5 h to obtain a pre-oxidized spun fabric.

[0043] (4) The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 800°C in an inert gas atmosphere, and then kept warm for 1.5 hours. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 20 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet; the inert gas is argon, and the nitrogen-containing gas is ammonia.

[0044] Example 5

[0045] (1) PAN and vanadium pentoxide are dissolved in DMF, with the mass ratio of PAN, vanadium pentoxide and DMF being 1:0.6:9, to obtain a spinning solution.

[0046] (2) The spinning solution obtained in step (1) is subjected to electrostatic spinning to obtain a spun product.

[0047] (3) The spun fabric obtained in step (2) is placed in an air atmosphere for heat treatment and pre-oxidation at a temperature of 200° C. for 2.5 h to obtain a pre-oxidized spun fabric.

[0048] (4) The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 900°C in an inert gas atmosphere, and then kept warm for 1 hour. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 50 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet; the inert gas is argon, and the nitrogen-containing gas is ammonia.

[0049] Example 6

[0050] (1) PAN and vanadium pentoxide are dissolved in DMF, with the mass ratio of PAN, vanadium pentoxide and DMF being 1:0.6:9, to obtain a spinning solution.

[0051] (2) The spinning solution obtained in step (1) is subjected to electrostatic spinning to obtain a spun product.

[0052] (3) The spun fabric obtained in step (2) is placed in an air atmosphere for heat treatment and pre-oxidation at a temperature of 200° C. for 3 h to obtain a pre-oxidized spun fabric.

[0053] (4) The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 900°C in an inert gas atmosphere, and then kept warm for 1 hour. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 10 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet; the inert gas is argon, and the nitrogen-containing gas is ammonia.

[0054] Comparative Example 1

[0055] Compared with Example 1, Comparative Example 1 removed vanadium pentoxide in step (1), and the remaining steps were the same as those in Example 1.

[0056] Comparative Example 2

[0057] Comparative Example 2 Compared with Example 1, the step (4) of Comparative Example 2 is changed to:

[0058] The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, introduced with an inert gas, heated to 900° C. in an inert gas atmosphere, and kept warm for 1 hour to obtain a positive electrode sheet; the inert gas is argon.

[0059] The remaining steps are the same as those in Example 1.

[0060] Comparative Example 3

[0061] Comparative Example 3 Compared with Example 1, the step (4) of Comparative Example 3 is changed to:

[0062] The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 900°C in an inert gas atmosphere and kept warm for 1 hour. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 120 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet; the inert gas is argon, and the nitrogen-containing gas is ammonia.

[0063] The remaining steps are the same as those in Example 1.

[0064] Performance tests were conducted on the above-mentioned multiple embodiments and comparative examples, and the test results are shown in Table 1. The data were obtained by testing a flexible zinc ion capacitor.

[0065]

[0066]

[0067] Table 1

[0068] It can be clearly seen from the above data that the positive electrode sheet prepared by the preparation method of the present invention is selected as the positive electrode of the capacitor. The positive electrode has a higher specific capacity and effectively improves the area specific capacitance of the capacitor, so that the specific capacitance of the capacitor can reach 459.5mF / cm 2, and significantly improves the cycle performance of the capacitor. After 10,000 cycles, its capacity retention rate can still be maintained at 97%. Such excellent cycle performance is very conducive to the promotion and application of the positive electrode and capacitor prepared by the preparation method of the present invention. By comparing Example 1 with Comparative Example 1, it can be seen that the specific capacity and area specific capacitance of Comparative Example 1 without vanadium composite are significantly lower than those of Example 1 with vanadium composite, which illustrates the higher zinc ion storage activity of vanadium nitride-vanadium oxide; comparing Example 1 with Comparative Example 2 and Comparative Example 3, Comparative Example 2 is a carbon fiber self-supporting electrode with only vanadium oxide composite, Comparative Example 3 is a carbon fiber self-supporting electrode with only vanadium nitride composite, and Example 1 is a carbon fiber self-supporting electrode with vanadium nitride and vanadium oxide composite, which shows higher specific capacity and area specific capacitance. More importantly, Example 1 shows a significantly higher cycle stability than Comparative Examples 2 and 3, confirming the synergistic effect formed between vanadium oxide and vanadium nitride, indicating that the heterojunction structure between vanadium oxide and vanadium nitride effectively enhances the structural stability of the electrode material, prevents structural collapse during the cycle, and significantly improves the cycle stability of the electrode.

[0069] The above description is merely a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any minor modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a flexible self-supporting positive electrode sheet, characterized in that: The following steps are included: (1) dissolving PAN and vanadium pentoxide in DMF, wherein the mass ratio of PAN, vanadium pentoxide, and DMF is 1: (0.2-0.6): 9, to obtain a spinning solution; (2) electrospinning the spinning solution obtained in step (1) to obtain a spun material; (3) placing the spun fabric obtained in step (2) in an air atmosphere for heat treatment and pre-oxidation, the heat treatment temperature is 200° C., and the heat treatment time is 1-3 hours to obtain a pre-oxidized spun fabric; (4) The pre-oxidized spinning product obtained in step (3) is transferred to a tubular furnace, an inert gas is introduced, and the product is heated to 800-1000°C in an inert gas atmosphere, and then kept warm for 1-2 hours. Subsequently, a nitrogen-containing gas is introduced, and after the inert gas is discharged, the product is kept warm for 1-50 minutes in a nitrogen-containing gas atmosphere to obtain a positive electrode sheet.

2. The method for preparing a flexible self-supporting positive electrode sheet according to claim 1, wherein: In the step (4), the inert gas is argon.

3. The method for preparing a flexible self-supporting positive electrode sheet according to claim 1, wherein: In the step (4), the nitrogen-containing gas is ammonia.

4. A flexible self-supporting positive electrode sheet, characterized in that: The flexible self-supporting positive electrode sheet is prepared by the preparation method of any one of claims 1 to 3.

5. A flexible zinc ion capacitor, characterized in that: The positive electrode sheet is the flexible self-supporting positive electrode sheet as claimed in claim 4; and the solid electrolyte is a PVA gel with zinc salt as the solute.

Citation Information

Patent Citations

  • Electrostatic spinning preparation method of vanadium-oxygen-carbon supercapacitor electrode material

    CN104389042A

  • Vanadium nitride (VN) porous hollow nano-fiber and preparation method thereof

    CN104532405A

  • Method for preparing metal nitrides through carbon nitride

    CN108793103A

  • Flexible self-supporting vanadium heptacarbide / nitrogen-doped porous carbon nanofiber composite material as well as preparation method and application of flexible self-supporting vanadium heptacarbide / nitrogen-doped porous carbon nanofiber composite material

    CN116111064A

  • Flexible self-supporting lithium-sulfur battery composite positive electrode material and preparation method thereof

    CN116487558A